2009
DOI: 10.1103/physrevd.80.094501
|View full text |Cite
|
Sign up to set email alerts
|

Gribov’s horizon and the ghost dressing function

Abstract: We study a relation recently derived by K. Kondo at zero momentum between the Zwanziger's horizon function, the ghost dressing function and Kugo's functions u and w. We agree with this result as far as bare quantities are considered. However, assuming the validity of the horizon gap equation, we argue that the solution wð0Þ ¼ 0 is not acceptable since it would lead to a vanishing renormalized ghost dressing function. On the contrary, when the cutoff goes to infinity, uð0Þ ! 1, wð0Þ ! À1 such that uð0Þ þ wð0Þ !… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 33 publications
6
66
1
Order By: Relevance
“…(2) is dominated by the first correction introduced by the nonvanishing dimension-two Landau-gauge gluon condensate [16][17][18][19][20][21], where the Wilson coefficient is applied at the O(α 4 )-order. In the previous methodological paper [3], we provided with a strong indication that the OPE analysis is indeed in order: it was clearly shown that the lattice data could be only explained by including non-perturbative contributions and that the Wilson coefficient for the Landau-gauge gluon condensate was needed to describe the behaviour of data above p 4 GeV and up to p 7 GeV (see next Fig.…”
Section: The Wilson Ope Coefficient and The Higher-power Correctionsmentioning
confidence: 99%
“…(2) is dominated by the first correction introduced by the nonvanishing dimension-two Landau-gauge gluon condensate [16][17][18][19][20][21], where the Wilson coefficient is applied at the O(α 4 )-order. In the previous methodological paper [3], we provided with a strong indication that the OPE analysis is indeed in order: it was clearly shown that the lattice data could be only explained by including non-perturbative contributions and that the Wilson coefficient for the Landau-gauge gluon condensate was needed to describe the behaviour of data above p 4 GeV and up to p 7 GeV (see next Fig.…”
Section: The Wilson Ope Coefficient and The Higher-power Correctionsmentioning
confidence: 99%
“…Both are nonperturbative definitions for the QCD running coupling, that have been extensively studied on the lattice [56][57][58][59][60][61]. Other MOM schemes based on different QCD vertices and kinematical configurations, as that for the ghost-gluon vertex [62][63][64][65], lead to alternative nonperturbative definitions although they can be related at any order in perturbation theory [66,67] …”
Section: Renormalization and The Running Couplingmentioning
confidence: 99%
“…It turns out that the dominant non-perturbative correction in Landau gauge is due to the non vanishing vacuum expectation value of the only dimension-two operator : A 2 ≡ A a µ A aµ [1], and that it is not small [2][3][4][5][6][7][8]. It is thus necessary to carefully look for the possibility of such a contribution, which appears in the OPE, as a 1/p 2 contribution up to logarithmic corrections.…”
Section: Introductionmentioning
confidence: 99%
“…The scheme for the anomalous dimension of Z A 2 is imposed through the renormalization of the local operator A 2 , as was done in ref. [2] to obtain its leading logarithm contribution, and it is only known in the MS at the order O(α 4 ) [29]. Then, that is the only possible choice of scheme for γ A 2 in eqs.…”
mentioning
confidence: 99%
See 1 more Smart Citation